THE DIPLOMATIC RELATIONS BETWEEN THE UNITED STATES AND MEXICO, AS AFFECTED BY THE STRUGGLE FOR RELIGIOUS LIBERTY IN MEXICO, 1925-1929 - Rice, M. Elizabeth Ann (1959)
LA OBRA ES UN FACSIMIL DEL ORIGINAL